Analysis Servant Leadership, Competence, and Motivation on Performance Employee: Study Literature Review - Candra Susanto, Primadi; Akbari Setiawan, Haikal; Yandi, Andri; Putri Amanda, Anggita; Gupron (Greenation International Journal of Law and Social Sciences, 2023)
The Effect of Servant Leadership, Competence and Motivation on Performance Employee is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley, and other academic online media. The research method with the research library comes from e-books and open-access e-journals. The results of this article: 1) Servant Leadership has an effect on Performance Employee; 2) Competence has an effect on the Performance of Employee; and 3) Motivation has an effect on Performance Employee.